International Wealth Effects - Jirka Slacalek (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper investigates the wealth effect for 16 industrial countries using the recently proposed technique that exploits the sluggishness of consumption growth. I estimate that the longrun marginal propensity to consume from wealth varies from less than 0.5 cents in France to 4.5 cents in the US. I document that the wealth effect tends to be larger in countries with more developed financial markets and has decreased in the last twenty years.
Keywords: E21; C22; E32; 330; wealth effect; income effect consumption dynamics sticky information